Peranan Taman Bacaan Masyarakat Pelangi Ilmu dalam Pemberdayaan Masyarakat di Desa Pematang Seleng: The Role of the Pelangi Ilmu Community Reading Park in Community Empowerment in Pematang Seleng Village - Tuzzahrah, Fadilla; Franindya Purwaningtyas (JBSI: Jurnal Bahasa dan Sastra Indonesia, 2025)
This study aims to analyze the role of TBM Pelangi Ilmu in community empowerment in Pematang Seleng village. The focus of this study is to identify the role, programs, and impacts in improving community empowerment in Pematang Seleng village. This study uses a descriptive qualitative method to understand community phenomena and their relationship with the research subjects. Data collection techniques in this study were carried out through in-depth interviews with the founder and manager of TBM Pelangi Ilmu regarding the role, programs, and impacts in improving community empowerment, as well as documentation. The results of the study indicate that there are several roles in community empowerment, and there are superior programs. The superior programs carried out by TBM Pelangi Ilmu are "Reading Corner" and "Mothers' Class Work," where this program aims to encourage the creation of better living conditions for the community. However, in implementing these programs, several obstacles are encountered in realizing this. Therefore, this study recommends that TBM Pelangi Ilmu collaborate with the government and the community. This research is expected to contribute to the development of a community literacy-based curriculum. Students will not only gain a better understanding of the role of TBM in empowering the community but also gain field experience by actively participating in the TBM program. This study concludes that the role of TBM in increasing community empowerment and its programs can run well. However, it requires support from the government and the community, both in the form of donations of collection materials and funds.